Cycle Related Kth Fibonacci Prime Labeling Of Graphs (International Journal of Food and Nutritional Sciences, 2022)
In this paper, we investigate the kth fibonacci prime labeling of two new families of graphs, which are a graph G is obtained by joining two cycles Cn and Cm by a path Ps and a graph G is obtained by joining two cycles Cn and Cm by a triangular snake Ts.